Pengembangan Ranah Afektif untuk Meningkatkan Pemahaman Konsep Pendidikan Agama Islam di SMA YA BAKII 1 Kesugihan - Muhammad Labib Ma’shum; Muh Hanif (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to describe the development of the affective domain in Islamic Religious Education learning at SMA Ya BAKII 1 Kesugihan Cilacap and find out the supporting and inhibiting factors for the development of the affective domain. The type of research used is qualitative research with qualitative descriptive method. Data collection is done through observation, interview, and documentation. Based on the research that has been carried out, it can be concluded that the development of the affective domain in Islamic Religious Education (PAI) learning has gone well. This development is carried out with a habituation approach, such as habituation of greetings, praying before and after learning, habituation of duha and duhur prayers in congregation, ziaroh muais, and istighosah. Supporting factors for the development of the affective domain consist of internal and external factors. Internal factors include students' own willingness to do good things, while external factors include a good family, a pesantren-based school environment with habituation and supporting infrastructure, and a good living environment such as pesantren. The inhibiting factors consist of internal factors, such as closed student personalities, low student willingness to learn, and unresponsive students, as well as external factors, such as bad living environment, less harmonious families, and unwise use of technology.